Lithic technographies of the middle holocene in the central region of South America: cultural tesserae for a paleo-historical mosaic (first part) - Viana, Sibeli A.; de M. Ramos, Marcos Paulo; Carbonelli, Juan Pablo; Costa, Kaira S. R. (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
This work, subdivided into the first part and the second part, produced a technographic overview of the lithic material of middle Holocene sites, located in the central portion of South America, in the macro-region dominated by savannas in the lowlands of South America. This analysis was possible through reflection on available bibliographic information. The description of the modes of making lithic tools was based on the recognition of the three technical principles based on the techno-functional perspective: debitage, shaping and affordance; and on the considerations about relationship between the active and prehensive parts of the pieces (also called “techno-functional categories”). As a result, a synthesis of the technological peculiarities and variabilities was obtained in areas little known or documented with regard to the lithic materiality. In the first part of the article, this overview highlighted that there was, in the groupings of the sites of the Cratón Amazônico, a localized contribution to the relative technical cultures on the part of the principles of debitage and shaping, without being completely homogeneous. In reference to the management of raw materials, a local supply of lithic resources can be seen near these sites.